Reliability and validity of the South African Triage Scale in low-resource settings - Dalwai, Mohammed K (Division of Emergency Medicine, 2018)
Emergency medical care (EMC) is proposed by the World Health Organization (WHO) as being one of the core components of a horizontal approach to improving population health in low-resource settings; triage is considered to be a fundamental part of this field. Most studies exploring triage have focused on high-income countries. In 2004, the Cape Triage Group (CTG) developed the South African Triage Scale (SATS) a scale that uses a physiologically based scoring system together with a list of discriminators - designed to triage patients into one of four priority groups for medical attention. The SATS was designed for use in the South African context to mitigate the limited numbers of doctors and professional nurses. The SATS has been implemented and assessed extensively in South Africa, but its performance across a spectrum of different low-resource settings, particularly non-sub-Saharan African and trauma-only settings, has not been adequately assessed. Médecins Sans Frontières (MSF), an international humanitarian organisation, introduced EMC in 2006 into low-resource settings. In 2011, MSF began introducing the SATS in various projects where it was providing EMC. Methodology: This was a multi-site retrospective cohort study which sought to assess the reliability and validity of the SATS in different low-resource settings. Aim 1: To implement and evaluate the SATS in Northern Pakistan by describing the steps of implementation and how accurate nurses were in using the triage scale. After one month of implementation, 370 triage forms from a one-week period were evaluated. Aim 2: To assess the inter- and intra-rater reliability and accuracy of nurse triage ratings when using the SATS in an emergency centre (EC) in Timergara, Pakistan. Fifteen EC nurses assigned triage ratings to a set of 42 reference vignettes (written case reports of EC patients) under classroom conditions. Inter-rater reliability was assessed by comparing these triage ratings; intra-rater reliability was assessed by asking the nurses to re-triage ten 12 random vignettes from the original set of 42 vignettes and comparing the duplicate ratings. Accuracy of the nurse ratings was measured against the reference standard. Aim 3: To improve the ability to measure reliability and validity in paediatric settings by developing a set of paediatric paper-based vignettes using the Delphi methodology. In a two-round consensus building process, a panel of EC experts were asked to independently triage 50 clinical vignettes using one of four acuity levels: emergency (patient to be seen immediately), very urgent (patient to be seen within 10 min), urgent (patient to be seen within 60 min), or routine (patient to be seen within four hours). The vignettes were based on real paediatric EC cases in South Africa. Vignettes that reached a minimum of 80% group consensus for acuity ratings on either round one or two were included in the final set of reference vignettes. Aim 4: To further assess the reliability of the SATS across MSF-supported hospitals using paper-based vignettes in Afghanistan, Haiti and Sierra Leone. Applying the same methodology as in Northern Pakistan, we assessed reliability under classroom conditions between December 2013 and February 2014. Aim 5: To assess the validity of the SATS across MSF-supported hospitals between June 2013 and June 2014. Validity was assessed by comparing patients’ SATS ratings with their final EC outcomes (i.e., hospital admission, death or discharge) across four sites in Afghanistan, Haiti and Sierra Leone. Findings The SATS was able to be easily implemented and accurately completed in a low-resource setting of Northern Pakistan. We recommended further implementation and assessment of reliability and validity in low-resource settings. Across six sites with a total of 87 nurses, including two trauma-only hospitals in Afghanistan and Haiti, a paediatric-only hospital in Sierra Leone and three mixed medical settings in Afghanistan, Pakistan and Haiti, the SATS demonstrated moderate to substantial reliability. Across all settings in which we measured validity using outcome markers, SATS predicted an increase in the likelihood of admission/death when moving from low- to high-triage acuity. In trauma-only settings of Afghanistan and Haiti, the SATS showed a 1-9% under-triage and 13 a 2-16% over-triage rate. In mixed medical and paediatric settings, under-triage ranged from 0-76% while over-triage ranged from 2-88%. A more logical standardised approach to assessing validity was put forward when using outcome markers that would allow easier comparisons to be done across validity studies irrespective of the number of levels the triage scale had. We developed a set of paediatric vignettes for use in low-resource settings but cautioned against its use after measuring reliability using adult reference vignettes. We found that generic vignettes were poor substitutes in a variety of settings based on a lack of contextualisation and understanding by local nurses. Conclusion: The SATS has reasonable reliability with good validity across different ECs in various lower-source settings. The SATS is a valid triage tool for prioritisation of patients with trauma in low-resource settings. Its use in mixed EC settings seems justified, but in paediatric settings context-specific adjustments and assessments of its performance would be prudent.